Christian Thomasius: logic as the doctrine of reason - Secundant, Sergiy (Sententiae, 2017)
In this article the Thomasius’s logic is estimated not from the point of view of formation of modern formal logic, but as one of the first attempts to create a non formal logic or a theory of the argument. His reform of logic was a part of his reform of the philosophy directed to release of the person from prejudices and to emergence of a new creative person. The author considers that Christian Thomasius’s logic cannot be regarded as a psychological or a juridical logic. It is rather an epistemological one that is focused mainly on a philosophical discourse. The purpose of such logic consists in delimiting true from false, probable from improbable. It is based on the anthropological bases. His anthropology is constructed on the epistemological principles of empiricism and performs critical functions: it is directed against a formalism and methodism of traditional logic. Understood as the doctrine about human reason, Thomasius’s logic is called to serve as a tool of the criticism in a substantive rational discourse, including philosophical, and it, as such, becomes basis of all his philosophy.